Ownership Structure, Board Structure And Performance In The Tunisian Banking Industry - Mnasri, Khadija (Asian Academy of Management (AAM), 2015)
The 2011 Tunisian revolution has played a role in bringing the corporate governance agenda to the forefront. This political change in Tunisia has revealed persistent governance problems in its banking industry. This paper presents the results of research conducted on how different aspects of corporate governance can influence bank performance. The sample comprises 10 Tunisian commercial banks for the period from 1997 to 2010. The performance-governance relationship is estimated using a range of econometric techniques. The findings reveal strong support for a negative association between blockholder ownership and performance. Our results show that the bank board size is related to directors' ability to monitor and advise management. Additionally, CEO duality is positively associated with performance. Further analysis suggests that the presence of government officials on banks' board of directors decreases bank performance. Taken together, our findings offer recommendations to regulators, especially for the on-going financial reform of corporate boards.